CURRENT ISSUES OF ENSURING FINANCIAL SECURITY IN MODERN CONDITIONS - Рузиева Диёра Сулаймановна (European Science Publishing, 2024)
This article discusses the topical problems of improving the database for obtaining electronic evidence in the internal affairs bodies in order to solve crimes of financial fraud in the field of modern payment systems. This article discusses current problems of improving the basis for obtaining electronic evidence in internal affairs bodies in order to solve crimes of financial fraud in the field of modern payment systems.
Keywords: economic crime, financial fraud, payment systems, payment organizations, digital expertise.